Impact of Leadership Styles on Decision-Making and Problem-Solving: Classical Faculty Leaders at Egyptian Governmental Universities - Gouda, Hanan (The Arab Journal of Administration, 2023)
Purpose - This study aims to investigate the impact of the common classical leadership styles (autocratic, democratic and laisser-faire) among faculty leaders at Egyptian governmental universities on their decision-making and problem-solving skills. Design/ methodology/approach - This study uses quantitative research approach; data was collected using structured questionnaires and analyzed using SPSS. The sample included 384 faculty members. Findings - Autocratic and democratic styles have a significant impact on decision-making and problem-solving skills. Laisser-faire style was found statistically insignificant on decision-making and problem-solving skills. Originality/value –The value of this study is that it provides insights on leadership styles and how they are perceived in governmental universities in Egypt. It enlightens the effective styles in terms of decision making and problem solving, therefore provides a framework for these universities. Leadership in higher education which is a vital issue today. Research implications: This research implies that the autocratic faculty leader- deemed ineffective in modern leadership theories-, is significant in governmental universities in matters of decision-making and problem-solving. Concerning the laisser-faire faculty leader, finding indicates that, this style is insignificant in governmental universities in terms of decision-making and problem-solving, contrarily to common belief, it was found that laisser-faire leaders are not effective in public governance in Egypt. The bureaucratic system that is applied in governmental universities in Egypt, leads to the autocratic and democratic style being more effective than laisser-faire.